Structural Evolution of Extended Continental Crust Deciphered From the Cretaceous Batholith in SE China, a Kinmen Island Perspective - Huang, Tsung-Han; Yeh, Meng Wan (Frontiers in Earth Science, 2020)
The continental crust of southeast Asia underwent from thickening, thinning to almost rifting during the Mesozoic era as the active continental margin transformed into a passive one. Such crustal thinning history is well-preserved in the Kinmen Island, as the lower crustal granitoids retrograded and rapidly exhumed to surface that were crosscuted by mafic dyke swarm. Kinmen Island is situated on the SE coast of Asia, featured by the widespread Cretaceous magmatism as the Paleo-Pacific plate subducted and rollbacked underneath the South China block. Although these complex magmatism are well reported and studied, their associated structural evolution and plate kinematics have not been clearly deciphered. Detailed field mapping, structural measurement, and petrographic analysis of the Kinmen Island were conducted. Up to five deformation events accompanied with five relevant magmatic episodes as well as their corresponding kinematic setting are reconstructed. The ~129 Ma Chenggong Tonalite (G1) preserved all deformation events identified in this study, which marks the lower bound timing of all reported events. D1 formed a gneiss dome with the Taiwushan Granite (~139 Ma) at the core bounded by moderately-dipping gneissic foliation (S1) as crust extended. D2 formed subhorizontal S-tectonite (S2) with further exhumation of D1 gneiss dome due to middle-to-lower crustal flow associated with further crustal thinning. D3 formed a sinistral ENE-WSW striking steeply S dipping shear belts with well-developed S/C/C’ fabrics. The moderately E-plunging lineation on C surface indicates its transtensional nature. Widespread garnet-bearing leucogranite (G2) associated with decompressional melting showed long lasting intrusion prior to D2 until post D3. D4 was the intrusion of biotite-bearing Tienpu Granite (~100 Ma; G3) that truncated G1, G2, and all fabrics, which was followed by the intrusion of E-W striking, steeply dipping biotite-bearing pegmatite (G4) as the crust further extended. The youngest deformation event (D5) was NE-SW striking subvertical mafic dyke swarm (G5; 90-76 Ma) due to mantle upwelling through significantly thinned crust. By integrating the structural evolution and the previously reported strain pattern, we delineate the slab rollback direction of the Paleo-pacific plate, which changed from northeastward (129~114 Ma) to southeastward (107~76 Ma). This plate kinematic movement switched during 114-107 Ma.